Designing for Motivation: Psychological Mediators of Gamified Engagement in Digital Knowledge Work - Prasetya, Yuli; Juwari; Arumsari, Andini Dwi (Data : Journal of Information Systems and Management, 2025)
Gamification is a common strategy in digital workspaces to boost engagement and performance. This study examines the psychological mechanisms of gamified engagement, particularly how badges, points, and leaderboards shape user motivation through Self-Determination Theory (SDT). Drawing on platform data from GitHub and Stack Overflow, combined with survey responses using the Intrinsic Motivation Inventory (IMI), the research examines whether gamification elements fulfill users' needs for competence, autonomy, and relatedness, thereby promoting knowledge creation and collaboration. The methodology combines behavioral data (1,500 user-week observations) with IMI survey responses (180 users), analyzed using structural equation modeling and mediation testing. Results indicate that gamification significantly enhances perceived competence and relatedness, which in turn mediate increases in knowledge sharing outputs and collaborative behavior. Competence is linked with content contributions, while relatedness correlates with social interaction metrics. Subgroup analysis reveals differential effects based on user roles and platform context. These findings highlight the importance of aligning gamification elements with psychological needs, rather than relying solely on extrinsic rewards. Ethical considerations, including role based design and data transparency, are essential for sustainable engagement. The study offers both theoretical insights and practical guidance for implementing motivationally effective and ethically sound gamified systems in professional digital environments.